Drawing attention to the dangerous - Kasderidis, Stathis; Taylor, John G.; Tsapatsoulis, Nicolas; Malchiodi, Dario (My University, 2003)
In this paper we present an architecture of attention-based control for artificial agents. The agent is responsible for monitoring adaptively the user in order to detect context switches in his state. Assuming a successful detection appropriate action will be taken. Simulation results based on a simple scenario show that Attention is an appropriate mechanism for implementing context switch detector systems.
Keywords: Neural networks (Computer science)--Congresses